Comparison of efficacy of visual inspection with 4% acetic acid, visual inspection with Lugol's iodine, Pap smear and colposcopy in screening cervical precancerous lesions - Bhattacharya, Apurba K.; Sarma, Hem K.; Das, Antara (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Background: Cervical malignancy is the fourth most common cancer in women worldwide. Screening of high-grade cervical intraepithelial neoplasia aids in early detection and their effective treatment which constitutes the most effective and widely used strategy to prevent cervical carcinoma throughout the world. Objectives of the study were to: screen women with visual inspection with 4% acetic acid (VIA), visual inspection with Lugol's iodine (VILI), Pap smear and colposcopy who have abnormal symptoms for unhealthy cervix; and to evaluate the sensitivity and specificity of VIA, VILI, Pap smear and colposcopy. Methods: This was a hospital based cross sectional study conducted at Jorhat Medical College, Assam at the department of obstetrics and gynaecology from June 2020 to May 2021, carried out on 60 women. This study was done on 60 women who fulfilled the inclusion and exclusion criteria, were first subjected to Pap smear followed by VIA, VILI, colposcopy and biopsy for confirmation of lesion, if needed. Data was obtained and statistically analyzed. Results: VIA showed sensitivity 96.15%, specificity 62.50% and diagnostic accuracy 88.23%. VILI showed sensitivity 89.65%, specificity 40% and diagnostic accuracy 82.35%. Colposcopy showed sensitivity 96.66%, specificity 25% and diagnostic accuracy 88.23%. Pap smear showed sensitivity of 86.66%, specificity 75% and diagnostic accuracy of 85.29%. Conclusions: Our study shows that VIA, VILI, Pap smear and colposcopy has comparable sensitivity. Pap smear shows better specificity. Therefore, use of combination of these tests gives better sensitivity and specificity for early detection of cervical carcinoma.